Soil fertility gradients and production constraints for coffee and banana on volcanic mountain slopes in the east African rift: a case study of Mt. Elgon - Bauw, P. de; Asten, Piet J.A. van; Jassogne, Laurence T.P.; Merckx, Roel (Elsevier, 2016)
Volcanic mountains in the East African Rift (e.g. Mt. Kenya, Mt. Kilimanjaro, Mt. Elgon) are some of the most productive agricultural regions, often dominated by coffee and banana cultivation. Consequently, these regions suffer from a high and increasing population density with a declining soil fertility status imposing pressure on the available land, which in turn results in encroaching into the national forests. This study documents the soil fertility constraints along the slopes of Mt. Elgon and explores its corresponding gradients in plant nutritional status. This research links the topography of Mt. Elgon to the prevailing soil types and their current fertility status. It reveals important relations and gradients between soil fertility parameters and its corresponding environment along the slope. Soil pH, soil available P and exchangeable K, Ca and Mg are significantly decreasing with elevation. Thereby, gradients and constraints in macro- and micro-nutrient uptake by coffee and banana are revealed along the toposequence and different altitude-specific nutrient limitations are determined for both crops. K, Mn and Si uptake in both crops is decreasing with elevation along the slope, while the Mo and Ni uptake in both crops is increasing. With increasing elevation, B uptake is only decreasing in coffee and P uptake is only decreasing in banana. In addition, the antagonistic interaction between K and Mg limits the Mg uptake of both crops in the lower areas, while in the high region the Mg uptake is simply limited by low soil availability. It follows that a general fertilizer recommendation cannot be made in these regions and that the soil fertility problems along these slopes should be specifically addressed and appropriately managed according to the local requirements.